2000
DOI: 10.1161/01.str.31.10.2295
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Profile and Early Outcome in Stroke Patients

Abstract: Background and Purpose-Experimental studies provide evidence of an association between ischemic stroke and increased oxidative stress, but data in humans are still limited and controversial. The purpose of this study was to investigate the time course of plasma antioxidant changes in ischemic stroke patients. Methods-Plasma antioxidants, including water-soluble (vitamin C and uric acid) and lipid-soluble (vitamins A and E) compounds as well as antioxidant enzyme activities in plasma (superoxide dismutase [SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
119
2
12

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 210 publications
(149 citation statements)
references
References 54 publications
16
119
2
12
Order By: Relevance
“…A recent study showed that in type 2 diabetic subjects elevated plasma UA levels were associated with increased arterial stiffness, which is a well-recognised cardiovascular risk factor [16]. Several studies in the general population showed an effect of serum UA levels on prediction of stroke outcomes [17][18][19]. Two studies have showed that elevated levels of UA were independently associated with an increased risk of early death after acute stroke [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that in type 2 diabetic subjects elevated plasma UA levels were associated with increased arterial stiffness, which is a well-recognised cardiovascular risk factor [16]. Several studies in the general population showed an effect of serum UA levels on prediction of stroke outcomes [17][18][19]. Two studies have showed that elevated levels of UA were independently associated with an increased risk of early death after acute stroke [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Leinonen et al (2000) reported an association between the plasma concentration of ascorbic acid and a-tocopherol and the degree of neurological impairment after ischaemic stroke . Cherubini et al (2000) also found evidence of reduced plasma antioxidant concentrations in ischaemic stroke patients and that higher plasma vitamin A and uric acid concentrations and lower plasma ascorbic acid concentrations and erythrocyte superoxide dismutase activity were associated with poor early clinical outcome. There is also some recent evidence of an association between oxidative damage and tissue inflammation as measured by C-reactive proteins (CRPs) in subjects with stroke disease (Gariballa et al, 2002).…”
Section: Introductionmentioning
confidence: 75%
“…The same study demonstrated an association between plasma total antioxidant activity and the volume of ischaemic cerebral infarction and the degree of subsequent neurological impairment. Another study of 38 ischaemic stroke patients and age and sex-matched controls reported reduced plasma antioxidant concentrations in stroke patients compared with controls and showed an association between poor antioxidant status and poor clinical outcome (Cherubini et al, 2000). Furthermore, Polidori et al (1998) reported a significant positive association between plasma lipid hydroperoxide concentration and the National Institute of Health Stroke Scale, and a significant negative correlation with the Glasgow Coma Scale (Polidori et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations